Implementation of the Food Traffic Light System to Improve Health Literacy Among Food Handlers in the Canteen of Politeknik Kesehatan Megarezky - Muhammad Ridha Afdhal; Nurul Mawaddah Syafitri; Nurgazali Nurgazali; Hairuddin K; Achmad Redha A (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The low literacy and health knowledge of food handlers have a significant impact on the health quality in canteens, both for consumers and the canteen environment itself. This study aims to improve the health knowledge and literacy of food handlers in canteens through the implementation of the Food Traffic Light System (FTLS). FTLS is a guide for selecting healthy food by adopting a traffic light system. This research is a quantitative study with a pre-experimental design using a one-group pre-test and post-test approach to assess the impact of training on health literacy and knowledge of the food traffic light system among food handlers at the canteen of Politeknik Kesehatan Megarezky. Pre-experimental research aims to test the effect of an intervention on characteristics of interest to the researcher. This study was conducted from September to December 2024 using validated questionnaires.The respondents in this study were 13 individuals working as food handlers. The data were analyzed descriptively using Microsoft Excel and SPSS 21. The paired t-test results for the literacy variable showed a Sig value of 0.000 (≤0.05), indicating an improvement in health literacy regarding the Food Traffic Light System before and after the training. Regarding knowledge, the paired t-test results also showed a Sig value of 0.000 (≤0.05), indicating a significant difference in knowledge before and after the training. This study emphasizes the importance of improving literacy and knowledge for food handlers to create a healthy canteen. Additionally, the study recommends conducting research with a larger sample and using complex method for future studies.Keyword: Food Traffic Light System, Healthy Canteen, Health Literacy, Health Promoting University